Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1055/s-0038-1651530
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Instrumentation Affects Perioperative Blood Loss in Total Knee Arthroplasty

Abstract: Patient-specific instrumentation (PSI) may contribute to reduced blood loss related to total knee arthroplasty (TKA). The purpose of this study was to compare the estimated hemoglobin (Hb) and red blood cell volume (RBC) losses in two groups of patients undergoing TKA with PSI and conventional instrumentation. Pre- and postoperative blood samples were collected from 22 patients randomly assigned to receive a PSI-assisted or conventional TKA. Post- to preoperative Hb difference was calculated and RBC loss was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(69 reference statements)
1
2
0
Order By: Relevance
“…The total blood loss, the red blood cell volume and the transfusion requirement did not differ between the two groups. This study also demonstrated that PSI leads to a significant trend in earlier haemoglobin regain 35 .…”
Section: Blood Losssupporting
confidence: 71%
See 1 more Smart Citation
“…The total blood loss, the red blood cell volume and the transfusion requirement did not differ between the two groups. This study also demonstrated that PSI leads to a significant trend in earlier haemoglobin regain 35 .…”
Section: Blood Losssupporting
confidence: 71%
“…Mehdipur et al and Menon et al report a shorter operational time in PSI group, however these results were not statistically significant 22,35 .…”
Section: Surgical Time and Cost-effectivenessmentioning
confidence: 85%
“…), which is not robust enough to determine the superiority of one over another. Furthermore, more randomized controlled trials (RCTs) have been published [10][11][12][13][14][15] recently and need to be integrated to update our knowledge (comprehensive comparison between our work and previous reviews can be found in S2 Supplemental file).…”
Section: Introductionmentioning
confidence: 99%
“…The variation in procedural steps between PSI-TKA and conventional TKA potentially leads to differences in surgical duration. This hypothesis is supported by several clinical trials [25,29,[42][43][44][45][46][47] and meta-analyses [41,48,49] that have reported a statistically significant decrease in surgical time with the PSI technique, ranging up to 20.4 minutes [45]. However, numerous other trials [50,51] and meta-analyses [7,10,28,36] have not found a significant difference in the duration of the procedures.…”
Section: Surgical Timementioning
confidence: 90%